The Repair of the Periorbital Soft Tissue - Köse, Rüştü (Fırat University, 2005)
Aims: The aim of this study is to discuss the repair and reconstruction methods of the periorbital soft tissue. Material and method: Periorbital soft tissue repair was performed in 51 patients. Fifty-nine repairs or reconstructions were carried out in soft tissues by primary repair, skin graft, local flaps, Z-plasty, W-plasty. The causes of the repair were 17 basal cell carcinomas, 2 epidermoid carcinomas, 17 traumas, 11 benign lesions and 4 scar tissues. Results: Successful results were obtained in primary repairs when reciprocal places sutured. Local flaps were preferred in tissue defects because of similar structure. Full thickness skin graft harvested from the back of the ear was chosen firstly in skin graft repairing and color harmony was achieved. Glabellar flaps that performed without thinning in two cases were detected thick in this region. Conclusion: Periorbital area comprises many important units despite being a little portion in whole body. Desired functional and aesthetic results may be attained to know the anatomy of this area, good evaluation the lesion preoperatively and choose the suitable repair method.

Amaç: Bu çalışmada periorbital bölgenin yumuşak dokularının tamir ve rekonstrüksiyon yöntemlerinin tartışılması amaçlanmıştır. Gereç ve yöntem: 51 hastaya periorbital yumuşak doku onarımı yapıldı. Yumuşak dokulara primer tamir, deri grefti, lokal flebler, Z-plasti ve Wplasti ile 59 onarım ve/veya rekonstrüksiyon yapıldı. Onarım gerektiren nedenler 17 bazal hücreli karsinom, 2 epidermoid karsinom, 17 travma, 11 benign lezyonlar, 4 skar dokusuydu. Bulgular: primer tamirlerde dokular uygun yerlerine dikildiğinde başarılı sonuçlar alındı. Doku defektlerinde lokal flebler benzer özellik taşıdığından ilk olarak tercih edildiler. Greftle onarımlarda ilk tercih olarak kulak arkasından tam kalınlıkta deri grefti kullanıldı ve iyi renk uyumu sağlandı. 2 vakada inceltilmeden uygulanan glabellar flebler bu bölge için kalın bulundu. Sonuç: Periorbital bölge vücudun küçük bir kısmını oluşturmasına karşın bir çok önemli yapıları içermektedir. İstenilen fonksiyonel ve estetik sonuçlara ancak bu bölgenin anatomisinin iyi bilinmesi, ameliyat öncesi lezyonun iyi değerlendirmesi yapılması ve uygun onarım yöntemi seçilmesi ile ulaşılır.
Periorbital Yumuşak Dokuların Onarımı